2009
DOI: 10.1117/12.824342
|View full text |Cite
|
Sign up to set email alerts
|

Progress of UV-NIL template making

Abstract: Nano-imprint lithography (NIL) has been counted as one of the lithography candidates for hp32nm node and beyond and has showed excellent resolution capability with remarkable low line edge roughness that is attracting many researchers in the industry who were searching for the finest patterning technology. Therefore, recently we have been focusing on the resolution improvement on the NIL templates with the 100keV acceleration voltage spot beam (SB) EB writer and the 50keV acceleration voltage variable shaped b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…1(a). Here, according to the typical aspect ratio of 2 for the UV nanoimprint mold 21) and the target line width of 90 nm, the depth of the shallow part was 180 nm. The depth of the deep part was 360 nm on the assumption of the pattern density variation of 2.…”
Section: Mold Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a). Here, according to the typical aspect ratio of 2 for the UV nanoimprint mold 21) and the target line width of 90 nm, the depth of the shallow part was 180 nm. The depth of the deep part was 360 nm on the assumption of the pattern density variation of 2.…”
Section: Mold Fabricationmentioning
confidence: 99%
“…In this work, we developed the process required for the fabrication of capacity-equalized molds with fine patterns while taking into account their compatibility with the currently existing mold fabrication processes [19][20][21] using electron beam (e-beam) lithography. We fabricated fine grooves with two-step depths by additional laser beam lithography and etching process to a typical mold fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…EBL is a well-known method for realizing a pattern with the highest resolution on a resist. [18][19][20][21] In our previous studies, the line and space (L=S) and bit pattern resolutions were enhanced by EBL using a polymer positive EB resist ZEP520A with a poor (low-solubility) solvent, such as a fluorocarbon and alcohol mixture, for resist patterning and by RIE for quartz patterning. It was shown that 12-nm-hp L=S and 22-nm-bp hole patterns were realized to have the highest resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] A master mold for NIL is generally made by electron beam lithography (EBL) for the ultimate pattern resolution. [15][16][17][18] A polymer positive electron beam (EB) resist ZEP520A, with a poor (low-solubility) solvent developer such as a fluorocarbon and alcohol mixture, has provided the best resolution, as far as we have studied, for the last 10 years. Its resolution limit was hp 16 nm in L/S patterns and bp 22 nm hole array for BPM in a large and practical patterning area, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%